Behavioural intention to use ICT in teaching science among lecturers in Nigerian Polytechnic - Bundot, Yohanna Garba (2018)
Nigeria is investing in information and communication technology (ICT) to improve students’ learning outcome and the quality of education. However, based on research literature, the use of computer in the teaching of science by lecturers is underutilised. Therefore, the study was conducted to investigate the intention to use computer in teaching science among lecturers in North Eastern Polytechnic. The study aimed at examining the relationship between perceptions, attitude, and other factors responsible for lecturer’s behavioural intention towards the use of computer in teaching science. A quantitative design followed by supporting interview was used to execute the study and address the research objectives. Two hundred and sixty-nine (269) lecturers were selected from a population of 715 lecturers. Quantitative data were obtained from the Technology Acceptance Model (TAM) inventory and the validated questionnaire was used in the study. The data were analysed using Structural Equation Modelling (SEM). Qualitative data were obtained using semi-structured interview protocol to facilitate interviews with five participants who were purposefully selected for this phase of the study. The qualitative phase of the study aimed at exploring important factors responsible for the intention to use ICT in science teaching. The findings showed the significance of perceived ease of use on perceived usefulness, perceived ease of use, and perceived usefulness are significant on attitude while perceived usefulness and attitude are significant on behavioural intention. Perceived ease of use was moderately significant towards behavioural intention against the TAM model. The moderators such as gender, age, and teaching experience showed influence on perceived ease of use, perceived usefulness, and attitude toward behavioural intention. Suggestions were made to provide incentives for lecturers who practise ICT and Trainings, workshops, and professional development courses should be provided to train lecturers on incorporating ICT in their teachings.